The relationship between corporate social responsibility and firm performance: evidence from Malaysia - Wan Yusoff, Wan Fauziah; Adamu, Muhammad Sani (Medwell Journals, 2016)
Corporate Social Responsibility (CSR) has been an important topic in accounting research. Despite extensive studies on CSR activities in Malaysia, studies that investigated the nature of CSR activities in relation to firm financial performance still limited. Thus, this research investigates the relationship between CSR activities and firm financial performance of Malaysian public listed companies. This study relied on secondary data obtained through content analysis of published company's annual reports for the year 2009-2013. Based on purposive sampling method, this study covered the assessment of the top one hundred companies in Malaysia whose names and shares were quoted in Malaysia stock exchange (Bursa Malaysia). Based on literature, four independent variables (environment, community, workplace and marketplace) and two dependent variables (Earning Per Share (EPS) and Return on Equity (ROE)) have been chosen in this study. Data were analyzed and interpreted using SPSS specifically Pearson's correlation to analyses the relationship between CSR activities and firm financial performance. This study discovered that most of the relationship between four CSR activities (environmental, community, marketplace and workplace) with financial performance (ROA and ROE) were positive. It can be concluded that Malaysian top 100 companies that actively involved in the four CSR activities are able to enhance their financial performance. It is imply that sound financial management can effectively be achieved through appropriate CSR practice that leads to a considerable economic development. Companies' performance would improve by adopting this appropriate recommendation for enhancing good CSR practice.